PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING BERBANTUAN INTERACTIVE E-BOOK TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA DI SDN 105289 KOLAM - Domi Yanti Sinaga; Nurhairani; Wildansyah Lubis (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to determine the effect of the Project Based Learning (PJBL) model assisted by an interactive e-book on the critical thinking skills of fourth-grade students at SDN 105289 Kolam in the topic of renewable energy sources. The study employed a quantitative approach using a one-group pretest-posttest design. The participants consisted of 30 fourth-grade students. Data were collected through a critical thinking skills test and classroom observation. The test was used to measure students’ critical thinking skills before and after the treatment, while observation was conducted to examine the implementation of the PJBL model assisted by an interactive e-book.The results showed that the mean pretest score of 50.67 increased to 88.67 in the posttest. The hypothesis testing using the Paired Sample t-Test revealed a significance value (Sig. 2-tailed) of less than 0.001, indicating a significant difference between the pretest and posttest scores. These findings demonstrate that the PJBL model assisted by an interactive e-book has a significant effect on students’ critical thinking skills. Observation results also indicated that students became more active in discussions, collaboration, problem-solving, and drawing conclusions during project activities. Therefore, the PJBL model assisted by an interactive e-book is effective in improving students’ critical thinking skills in science learning, particularly on the topic of renewable energy sources.